An image sensor with fast objects' position extraction function. - Akita, J.
This paper describes a kind of vision chip, which is an integration of an image processing circuit with photoreceptors, that has a function of extracting objects' positions in focal plane. The objects' positions are output as their coordinates, which are useful for further detailed image recognition processing. The extraction processing has two steps; first, the flags indicating the objects' center positions are generated by analog parallel processing circuit implemented by resistive network and comparators, and next, the coordinates of such flags are generated by x- and y-priority encoders and a novel successive masking circuit. The designed circuit is capable of centroid detection for 23 × 23 pixels within 50 μs, and the processing time is expected not to increase so much even if the number of pixels increases, which will represent an improvement over the conventional processor-based image processing system. We also proposed and evaluated another implementation of a centroid detector using pulse-width adder.
Keywords: 23 pixel; 50 mus; 529 pixel; CCD; Analog parallel processing circuit; Centroid detection; Comparators; Focal plane; Image recognition processing; Image sensor; Photoreceptors; Position extraction function; Processing time; Pulse-width adder; Resistive network; Successive masking circuit